Optimal dietary concentration of vitamin E for alleviating the effect of heat stress on performance, thyroid status, ACTH and some serum metabolite and mineral concentrations in broilers - Şahin, Kazım; Küçük, Ömer; Şahin, Nurhan; Gursu, MF (Czech Academy Agricultural Sciences, 2002)
An experiment utilizing Cobb-500 male broilers was conducted to evaluate the effects of vitamin E (d1-alpha-tocopheryl acetate) supplementation at various concentrations (0, 62.5, 125, 250, or 500 mg/kg of diet) on performance and serum concentrations of Triiodothyronine (T-3) Thyroxin (T-4) Adrenocorticotropine Hormone (ACTH), and some metabolites and minerals in broilers reared under heat stress (32degreesC). One day-old 150 male broilers were randomly assigned to 5 treatment groups, 3 replicates of 10 birds each. The birds received either a basal diet or basal diet supplemented with vitamin E at 62.5, 125, 250, or 500 mg/kg of diet. Increased supplemental Vitamin E linearly increased feed intake (P = 0.01), live weight gain (P = 0.01), and improved feed efficiency linearly (P = 0.001). Increasing dietary vitamin E supplementation also resulted in linear increases in serum T 3 and T 4 concentrations (P = 0.01) but, linear decreases in ACTH concentration (P = 0.01). Serum glucose, uric acid, triglycerides, and cholesterol concentrations decreased linearly (P = 0.001) while, protein and albumin concentrations increased linearly (P = 0.001) when dietary vitamin E supplementation increased. Serum activities of Serum Glutamic Oxalate Transaminase (SGOT) and Serum Glutamic Pyruvate Transaminase (SGPT) were not influenced by dietary vitamin E supplementation (P > 0.10). However, serum activity of Alkaline Phosphatase (AP) increased linearly (P = 0.001) with increasing dietary vitamin E supplementation. Increasing dietary vitamin E supplementation also caused linear increases (P = 0.001) in serum concentrations of Ca and P. Results of the present study conclude that a 250 mg/kg of vitamin E provides an optimal performance in broiler chicks reared under heat stress, and vitamin E supplementation at such a level can be considered as a protective management practice in a broiler diet, reducing the negative effects of heat stress.
Keywords: thyroxin; triiodothyronine; chicken; vitamin E; nutrition; heat stress